2021
DOI: 10.1002/chir.23290
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐selective electron transmission through self‐assembled monolayers of double‐stranded peptide nucleic acid

Abstract: Monolayers of chiral molecules can preferentially transmit electrons with a specific spin orientation, introducing chiral molecules as efficient spin filters. This phenomenon is established as chirality-induced spin selectivity (CISS) and was demonstrated directly for the first time in self-assembled monolayers (SAMs) of double-stranded DNA (dsDNA) 1. Here, we discuss SAMs of double-stranded peptide nucleic acid (dsPNA) as a system which allows for systematic investigations of the influence of various molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In a similar vein, Zwang et al ., showed that changing the DNA helix from the right‐handed B‐DNA structure to a left‐handed Z‐DNA, caused the preferential spin transport to switch from anti‐parallel to parallel, respectively [70] . Analogous studies with peptide‐nucleic acid (PNA) helices show a similar change in preferred SP when comparing left‐handed M‐PNA to right‐handed P‐PNA; see Table 5 [71] …”
Section: Resultsmentioning
confidence: 94%
“…In a similar vein, Zwang et al ., showed that changing the DNA helix from the right‐handed B‐DNA structure to a left‐handed Z‐DNA, caused the preferential spin transport to switch from anti‐parallel to parallel, respectively [70] . Analogous studies with peptide‐nucleic acid (PNA) helices show a similar change in preferred SP when comparing left‐handed M‐PNA to right‐handed P‐PNA; see Table 5 [71] …”
Section: Resultsmentioning
confidence: 94%
“…While these explorative approaches have proven successful, the origin of the electron spin polarization in the chiral oxide layers is not yet understood. Direct electron polarimetry established CISS so far for helical organic molecules such as DNA, , PNA, oligopeptides, and helicene . To promote the well-targeted improvement of these catalyst systems, an understanding of the spin-polarizing mechanism in the chiral oxide layers is required.…”
mentioning
confidence: 99%
“…Very recently, ds peptide nucleic acids (PNAs) have been proposed to study the CISS effect. Their spin-filtering capabilities were directly correlated to the molecular helicity, highlighting the worth of the dsPNAs for systematic studies of the CISS effect ( Möllers et al, 2021 ).…”
Section: Main Supramolecular Structures Where Ciss Effect Has Been Studiedmentioning
confidence: 99%